Perlindungan Hukum bagi Pemilik Hak Guna Perkebunan Tanah yang Terkena Pembebasan Lahan Pertambangan - Miriam Hijriyani; F. X. Arsin Lukman; Zulfadli Barus (CV Rewang Rencang, 2025)
Legal protection and legal certainty for landowners is also a crucial issue in the process of land acquisition. Although Law No. 2 of 2012 has set up a mechanism for indemnity, in practice, dissatisfaction often arises on the part of landowners. This is due to various factors, including the lack of transparency in the land valuation process, the mismatch of the indemnity value with the market value, as well as the lack of efforts to restore the socio-economic conditions of the affected communities. Juridically, land acquisition derived from Hak Guna Usaha (HGU) for mining activities cannot be implemented through the land acquisition mechanism based on Law No. 2 of 2012, unless the activity is qualified as public interest by the government. Therefore, the use of HGU land for mining must be based on the consent of the rights holder and set forth in a valid cooperation agreement as stipulated in Article 29 letter c and Article 30 paragraph (2) of Government Regulation Number 18 of 2021. The Joint Land Use Agreement (PPLB) scheme is a legally recognized alternative instrument to resolve the overlap between mining business licenses (IUP) and HGUS, as long as it is prepared by meeting the legal requirements of the agreement under Article 1320 of the Civil Code, based on the principle of freedom of contract, and does not conflict with laws and regulations.